Comparative survey of parents\'BMI in obese and non-obese ‎‏6‏‎ - ‎‏12‏‎ year old ‎children in Esfahan, ‎‏2000‏ - nasrin akbari; khosro tavakol; neda parvin; masoumeh delaram; afsaneh kazemiyan (Guilan University of Medical Sciences, 2005)
Introduction: Child obesity is an issue which deserves attention because it can cause medical ‎problem in children and adults and it tends to sustain which becomes chronic and causes ‎several health risks in adulthood. In recent years, the increasing prevalence of obesity in ‎children has become an important issue in different parts of world. Therefore diagnosis of ‎child obesity is essential in pediatric.‎ Preventive medicine and the best way are to acknowledge and limit the risk factors.‎ Objective: This study aims to determine and compare parents, BMI in obese and non - obese ‎‏6-12‏‎ year old children in Esfahan in ‎‏2000‏‎.‎ Methods: In this descriptive case-control study, ‎‏150‏‎ obese ,‎‏6-12‏‎ year old children were ‎matched as regard to age, sex and place of living with same number of non-obese children and ‎their BMI and their parents, BMI were compared.‎ Results: Findings indicated that there is a significant relation between parents, BMI and ‎children,s obesity and their BMI was higher than the BMI of non-obese children,s parents.In ‎another word, obese children 's parents were more obese and had more extra weight that the ‎non- obese children ,s parents. ‎ Conclusion:Since there was a significant relationship between parents, obesity and their ‎children ,s obesity and parents, obesity is an important risk for children ,s obesity, therefore it is ‎suggested to promptly improve parents, knowledge on obesity and its risks and stages of ‎prevention of children ,s obesity.‎